Application of in situ direct shear device to shear strength measurement of rockfill materials - Si-hong Liu (Water Science and Engineering, 2009)
A simplified in situ direct shear test (DST) was developed for measuring the shear strength of soils in fields. In this test, a latticed shearing frame replaces the upper half of the shear box used in the conventional direct shear box test. The latticed shearing frame is directly embedded in the ground to be tested after a construction process and is pulled with a flexible chain while a constant dead load is applied to the sample in the shearing frame. This simplified in situ DST has been validated by comparing its results with those of triaxial tests on samples with parallel gradations under normal stresses less than 100 kPa. In this study, the DST was further validated by carrying out tests on samples with the same gradations, rather than on samples with parallel gradations, under normal stresses up to 880 kPa. In addition, the DST was performed inside fills in two applications.